Discourse, affect and the ethics of subjectivity - Keränen, Hannele; Lapin yliopisto. Yhteiskuntatieteiden tiedekunta (Rovaniemi : Lapin yliopisto = University of Lapland, 2018)
Tiivistelmä.
I Starting points -- Justification for the study -- Research questions -- Key concepts -- Theoretical and methodological departures -- Data and analysis -- Structure of the thesis -- II Discourse, ethical subjectivity and affect -- Using Foucault to study ethical subjectivity -- Strategy discourse and subjectivity -- Affect and ethical subjectivity -- III Governmentality, strategic profiling and subjectivity in higher education -- Transforming the political rationalities of higher education -- The changing nature of the Finnish higher education -- The becoming of subjects in higher education -- IV Methodology -- Pursuing auto-ethnography -- Empirical material -- Employing reflexivity -- The reliability of the study -- Introduction of the case organisation Futuria -- V Discourse and the ethics of subjectivity -- Sustaining 'the business-as-usual' -- Becoming the northern forerunner -- VI Affect and the ethics of subjectivity -- Bridging affect to self-production -- Becoming a Devil’s advocate -- Affective dissonance and self-production -- Towards an ethic of recognition? -- VII Discussion and conclusions -- Discussion of the research findings -- Conclusions of the thesis.
Väitöskirja
Keywords: etiikka; toimijuus; affektiivisuus; diskurssi; itse; korkea-asteen koulutus; autoetnografia; etik; agentskap; affektivitet; diskurs; självet; utbildning på högskolenivå; autoetnografi; korkeakoulut; ammattikorkeakoulut; yhdistyminen; organisaatiomuutokset; henkilöstö; johtajat